Directing the migration of serum-free, ex vivo-expanded Vγ9Vδ2 T cells - Parwani, Kiran K.; Branella, Gianna M.; Burnham, Rebecca E.; Burnham, Andre J.; Bustamante, Austre Y. Schiaffino; Foppiani, Elisabetta Manuela; Knight, Kristopher A.; Petrich, Brian G.; Horwitz, Edwin M.; Doering, Christopher B.; Spencer, H. Trent (Frontiers in Immunology, 2024)
Vγ9Vδ2 T cells represent a promising cancer therapy platform because the implementation of allogenic, off-the-shelf product candidates is possible. However, intravenous administration of human Vγ9Vδ2 T cells manufactured under GMP-compliant, serum-free conditions are not tested easily in most mouse models, mainly because they lack the ability to migrate from the blood to tissues or tumors. We demonstrate these T cells do not migrate from the circulation to the mouse bone marrow (BM), the site of many malignancies. Thus, there is a need to better characterize human γδ T cell migration in vivo and develop strategies to direct these cells to in vivo sites of therapeutic interest. To better understand the migration of these cells, and possibly influence their migration, NSG mice were conditioned with agents to clear BM cellular compartments, i.e., busulfan or total body irradiation (TBI), or promote T-cell migration to inflamed BM, i.e., incomplete Freund's adjuvant (IFA), prior to administering γδ T cells. Conditioning with TBI, unlike busulfan or IFA, increases the percentage and number of γδ T cells accumulating in the mouse BM, and cells in the PB and BM display identical surface protein profiles. To better understand the mechanism by which cells migrate to the BM, mice were conditioned with TBI and administered γδ T cells or tracker-stained red blood cells. The mechanism by which γδ T cells enter the BM after radiation is passive migration from the circulation, not homing. We tested if these ex vivo-expanded cells can migrate based on chemokine expression patterns and show it is possible to initiate homing by utilizing highlyexpressed chemokine receptors on the expanded γδ T cells. γδ T cells highly express CCR2, which provides chemokine-attraction to CCL2-expressing cells. IFNγ-primed MSCs (γMSCs) express CCL2, and we developed in vitro and in vivo models to test γδ T-cell homing to CCL2-expressing cells. Using an established neuroblastoma NSG mouse model, we show intratumoral-injected γMSCs increase the homing of γδ T cells to this tumor. These studies provide insight into the migration of serum-free, ex vivo-expanded Vγ9Vδ2 T cells in NSG mice, which is critical to understanding fundamental properties of these cells.